Concept of attitudes in the system of scientific knowledge of social psychology - Tatarko, Kristina I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
This article presents a theoretical analysis of the concept of «attitudes». Despite the long history of research of this concept, there are some unsolved questions in this area of knowledge. In the scientific community, there are ambiguous positions in the correlation of this category to the terms «attitude», «prejudice», «social stereotype», which can make it difficult to study the attitudes. The main reasons for this uncertainty are indicated. The semantic content of these concepts is delineated through their comparison. Unresolved issues in the study of attitudes have been identified.
Keywords: attitude; prejudice; social stereotype